Recurrent somatic embryogenesis and plant regeneration in Angelica glauca Edgew., a critically endangered medicinal plant of the Western Himalaya - Pandey, Meena; Dhar, Uppeandra; Samant, Sher Singh; Shirgurkar, Mrudul Vijay; Thengane, Shubhada Ratnakar (Journal of Horticultural Science & Biotechnology, 2011)
Secondary somatic embryogenesis and plant regeneration from seedling explants of Angelica glauca, an endangered medicinal plant of the Himalaya, is reported for the first time. Callus was obtained from all the explants tested in the present study (i.e., epicotyls, hypocotyls, and cotyledonary nodes). The highest frequency of callus formation (95.8%) was observed using epicotyl explants on 4.0 mu M 2,4-dichlorophenoxyacetic acid (2,4-D), whereas 70.8% of hypocotyl explants, and 58.3% of cotyledonary nodes produced callus. One-hundred percent embryogenic callus was induced from epicotyl explants in 2.0 mu M 6-benzyladenine (BA) and 2.0 mu M alpha-naphthaleneacetic acid (NAA), together with the maximum number of somatic embryos (34.2 embryos per explant). Cotyledonary nodes did not produce somatic embryos. Histological studies confirmed the induction of somatic embryogenesis. Somatic embryos germinated into plantlets upon transfer to half-strength Murashige and Skoog (MS) medium without added plant growth regulators. We observed 85% survival of these plantlets under field conditions. The development of secondary embryos was also observed when primary embryos were sub-cultured on full-strength MS medium containing 2.0 mu M NAA plus 2.0 mu M BA. This system of recurrent somatic embryogenesis provides a route for gene transfer and also for the large-scale production of this critically endangered medicinal plant.

Combinatorial approach through in vitro regeneration and phytochemical profiling of ceropegia media (huber) ans.: a potential way forward in the conservation of an endangered medicinal plant from the western ghats in India - Pandey, Meena; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Punekar, Sachin A.; Giri, Ashok P. (Journal of Plant Growth Regulation, 2020)
Ceropegia mediais an endemic and endangered plant as its propagation through seeds is unreliable due to low germination, slow growth and seedling decay under natural conditions. Also, tubers of this plant are edible serving as carbohydrate source with medicinal values leading to severe population decline in the natural habitat. To provide a sustainable solution, an efficient in vitro propagation protocol along with phytochemical profiling was developed forC. media. Callus cultures were induced from seedling and wild leaf tissues using the most effective Murashige and Skoog's (MS) medium with 2,4-dichlorophenoxyacetic acid (2,4-D; 2 mu M) and sucrose (3%). Somatic embryos were acquired on MS medium with 1 mu M 6-Benzylaminopurine (BAP) and 1 mu M 2,4-D. Conversion into plantlets was attained only from tissue culture-derived seedling leaf (TCDSL) explant. Further, in vitro tuberization was achieved from TCDSL callus with BAP and Naphthalene acetic acid (NAA). AgNO(3)as an elicitor had a positive effect on both fresh and dry weights of callus. Successful acclimatization (58%) was attained after two months resulting in normal phenotype in pots. Further, metabolite profiles of ten different tissues from wild and in vitro plants were compared. Total 82 compounds comprising alkaloids, fatty acids, fatty acid ester, steroids, terpenes and hydrocarbons were identified. Overall, results suggested enhanced production of selected metabolites with in vitro propagation and AgNO3, alleviating the problem of unavailability of planting materials. Thus, the current study might offer potential ways for the conservation of such RED enlisted species asC. media. [GRAHICS]
Keywords: Ceropegia media; GC-MS; Microtuberization; Secondary metabolites; Silver nitrate; somatic embryogenesis

Comprehensive tissue specific analysis of antioxidant potential and metabolite profiling of a vulnerable therapeutic herb Ceropegia sahyadrica - Pandey, Meena; Dholakia, Bhushan B.; Saraf, Purva S.; Punekar, Sachin A.; Giri, Ashok P. (3 Biotech, 2025)
This study investigated tissue-culture of an endangered medicinal herb, Ceropegia sahyadrica, along with tissue-specific variation in antioxidant activity and GC-MS based phytochemical profiling using wild and in vitro explants. In vitro leaf explants exhibited callus induction rate of 100% in Murashige and Skoog media containing 6-benzylaminopurine (4 mu M) and 2,4-dichlorophenoxyacetic acid (2 mu M) with 5% sucrose, whereas in vitro root explant achieved 66.7% with the combination of 2 mu M 6-benzylaminopurine and 1 mu M 2,4-dichlorophenoxyacetic acid in Murashige and Skoog medium. Microtuberization was most pronounced in in vitro root explants with a maximum response of 73.3% in 1 mu M indole-3-acetic acid, 2 mu M 6-benzylaminopurine and 5% sucrose. Scanning electron microscopy imaging revealed distinct cellular organization among tissues. Further, antioxidant potential assessed through 1,1-diphenyl-2-picrylhydrazyl radical scavenging assays and estimated total phenolic content showed metabolic variation and commonality between in vitro and wild tissues. Additionally, phytochemical profiling by gas chromatography-mass spectrometry identified 201 compounds, including alkaloids, fatty acid methyl esters, flavonoids, phytosterols and other bioactive molecules with alterations in metabolite profiles between in vitro and wild tissues. These findings demonstrated that explant origin and culture condition might significantly influence metabolic responses for conservation and ensures a reliable source of bioactive compound.
Keywords: Ceropegia- Conservation; Endemic medicinal herb; GC-MS; Metabolite profiling; Tuberization